Rice Farmers' Perception of Climate Change in Demak Regency (A Multiple Regression Analysis) - Khotimatul Barki; Joko Mariyono; Siwi Gayatri (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
Climate change significantly impacts the agriculture and food security sectors, especially in vulnerable areas such as Demak Regency, Central Java. In Demak Regency, frequent climate disruptions like floods and erratic weather have reduced rice yields and raised crop failure rates. This study aims to analyze rice farmers' perceptions of climate change and the factors that affect it, including age, gender, education, farming experience, production, and location. This study was conducted between December 2024 and February 2025. The method of this study is a descriptive quantitative survey with a sample of 160 farmer respondents selected purposively from coastal and non-coastal areas. Data were collected through interviews and observations. The data analysis used was multiple linear regression with SPSS 26. The results show that farmers' perceptions in coastal areas are higher than those of non-coastal areas. Age and location had a significant positive effect, while gender, education, farming experience, and production harmed the perception of climate change risk. Female farmers have higher perceptions than men, while farmers with higher education, experience, and production tend to feel safer, so the perception of risk regarding climate change decreases.